Reward for Luck in a Dynamic Agency Model - Hoffmann, Florian; Pfeil, Sebastian (Review of Financial Studies, 2010)
[This article studies a continuous time principal-agent problem of a firm whose cash flows are determined by the manager's unobserved effort. The firm's cash flows are further subject to persistent and publicly observable shocks that are beyond the manager's control. While standard contracting models predict that compensation should optimally filter out these shocks, empirical evidence suggests otherwise. In line with this evidence, our model predicts that the manager is "rewarded for luck."]